Insecticide susceptibility status and resistance mechanism of Anopheles cracens Sallum and Peyton and Anopheles maculatus Theobald (Family: Culicidae) from knowlesi malaria endemic areas in Peninsular Malaysia - Rohani, Ahmad; Aidil Azahary, Abdul Rahman; Yu, Ke-Xin; Nor, Zurainee Mohamed; Wan Najdah, Wan Mohamad Ali; Lee, Han Lim (Medknow Publications, 2019)
Objective: To assess the insecticide susceptibility status of Anopheles cracens (An. cracens) and Anopheles maculatus (An. maculatus) from knowlesi malaria endemic areas in Peninsular Malaysia towards DDT, malathion and deltamethrin and to determine the resistance mechanism involved. Methods: Adult and larval mosquitos were collected for surveillance. Susceptibility status of Anopheles was determined using the standard WHO adult bioassay, larval bioassay and biochemical enzyme assay. Results: WHO adult bioassay results indicated An. cracens collected from Kampung Sungai Ular, Pahang was resistant towards 4% DDT, while An. maculatus collected from Kampung Sokor, Kelantan and Kampung Sungai Lui, Selangor exhibited resistance towards 4% DDT. However, the enzyme activity profiles varied according to strains and species. The resistance ratio of larval bioassay, showed that all strains and species tested were susceptible to malathion and temephos. Conclusions: Since only a few anopheline strains exhibited low level of insecticide resistance towards malathion, DDT and temephos. These insecticides are still considered effective for vector control program towards An. cracens and An. maculatus. © 2019 Asian Pacific Journal of Tropical Medicine Produced by Wolters Kluwer-Medknow.